1999
DOI: 10.1007/s004240050841
|View full text |Cite
|
Sign up to set email alerts
|

ATP acting on P 2Y receptors triggers calcium mobilization in primary cultures of rat neurohypophysial astrocytes (pituicytes)

Abstract: The effect of adenosine triphosphate (ATP) on the intracellular Ca2+ concentration ([Ca2+]i) of cultured neurohypophysial astrocytes (pituicytes) was studied by fluorescence videomicroscopy. ATP evoked a [Ca2+]i increase, which was dose dependent in the 2.5-50 microM range (EC50=4.3 microM). The ATP-evoked [Ca2+]i rise was not modified during the first minute following the removal of external Ca2+. Application of 500 nM thapsigargin inhibited the ATP-dependent [Ca2+]i increase. Caffeine (10 mM) and ryanodine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…duction is mediated by phospholipase C activated after P2Y 1 receptor activation (Troadec et al, 1999). However, in the CA3 interneurons, U-73122, an inhibitor of phospholipase C, did not significantly affect the IPSC frequency increase by 2meSATP at a larger concentration (10 M) than that completely abolishes [Ca 2ϩ ] i changes in the astrocytes (0.5-1 M) (Idestrup and Salter, 1998;Troadec et al, 1999;Koizumi et al, 2002).…”
Section: Activation Of P2y 1 Receptors Activates Inward Currents In Imentioning
confidence: 87%
See 1 more Smart Citation
“…duction is mediated by phospholipase C activated after P2Y 1 receptor activation (Troadec et al, 1999). However, in the CA3 interneurons, U-73122, an inhibitor of phospholipase C, did not significantly affect the IPSC frequency increase by 2meSATP at a larger concentration (10 M) than that completely abolishes [Ca 2ϩ ] i changes in the astrocytes (0.5-1 M) (Idestrup and Salter, 1998;Troadec et al, 1999;Koizumi et al, 2002).…”
Section: Activation Of P2y 1 Receptors Activates Inward Currents In Imentioning
confidence: 87%
“…However, in the CA3 interneurons, U-73122, an inhibitor of phospholipase C, did not significantly affect the IPSC frequency increase by 2meSATP at a larger concentration (10 M) than that completely abolishes [Ca 2ϩ ] i changes in the astrocytes (0.5-1 M) (Idestrup and Salter, 1998;Troadec et al, 1999;Koizumi et al, 2002). In the absence and presence of U-73122, IPSC frequency increased from 3.0 Ϯ 1.3 to 8.1 Ϯ 0.7 Hz and from 2.8 Ϯ 1.3 to 8.5 Ϯ 0.9 Hz, respectively (n ϭ 4; p ϭ 0.72), suggesting that increase in IPSC frequency does not involve phospholipase pathways, in a similar manner to that reported for recombinant P2Y 1 receptors expressed in the oocytes, which is linked to unidentified cation conductance (O'Grady et al, 1996).…”
Section: Activation Of P2y 1 Receptors Activates Inward Currents In Imentioning
confidence: 96%
“…Cell culture Pituicytes cell cultures were prepared from adult male Wistar rats (150-200 g) and maintained in primary cultures as previously described by Hatton et al [12] and modified by Troadec et al [39]. Briefly, rats were asphyxiated by CO 2 and killed by decapitation with a guillotine following the guidelines laid down by the French/European ethics committee.…”
Section: Methodsmentioning
confidence: 99%
“…The neurohypophysial astrocytes, called pituicytes, are intimately associated with nerve terminals, and we have recently shown that in these cells extracellular ATP induces an increase in the concentration of free cytosolic calcium ([Ca 2+ ] i ) via a P 2Y purinoceptor [39]. The physiological significance of this ATP-induced [Ca 2+ ] i increase in cultured pituicytes remains largely unknown.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation